SKRINING FAKTOR RISIKO DAN RIWAYAT PENYAKIT TIDAK MENULAR - Arifin, Zaenal; Dewi Nursukma Purqoti; Baiq Ruli Fatmawati; Ilham; Dian Istiana (Fakultas Pertanian, 2025)
Non-communicable diseases [NCDs] have now become one of the most common causes of death, namely around 73% of all deaths. Non-communicable diseases can be influenced by non-modifiable risk factors and modifiable risk factors. Efforts to prevent and control NCDs can be carried out through promotive and preventive means. The purpose of this community service is to find out the risk factors and history of NCDs of the participants. The community services is implemented through identification of risk factors and history of NCDs through examination of several NCD indicators and preparation of a NCD risk factor monitoring book. The results of the implementation of community service activities [PkM] on risk factors and history of non-communicable diseases [PTM] obtained the results of the examination of one of the NCD indicators in several individuals, it was found that the average cholesterol level was above normal. And based on the results of the identification of the history of non-communicable diseases that are most commonly experienced in the family is hypertension, which is 41.9%. Based on the results of the implementation of this PKM activity, it is hoped that participants are able and willing to make efforts to prevent NCDs through early detection or regular screening using the NCD risk factor monitoring book.